1999
DOI: 10.1177/088572889902200102
|View full text |Cite
|
Sign up to set email alerts
|

Research Translated into Practices for Increasing Student Involvement in Transition-Related Activities

Abstract: This article describes an empirical investigation of the process and outcomes associated with research-to-practice strategies in three schools during a three and a half-year project. The three interrelated phases of the process were (a) the establishment of an empirical foundation, (b) the design and implementation of school-based interventions, and (c) the evaluation of the effectiveness of the interventions. Findings from each phase are described. The benefits and limitations of research-to-practice strategi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…In contrast, the large-scale studies involving parents have provided few findings related to parent involvement in the transition process or post-school life for the young adult with disability and their families. In the United States, research has been focused on areas such as parent involvement in transition planning (e.g., Geenen, Powers, & Lopez-Vasquez, 2001), evidence-based practices for increasing student involvement in the transition process (e.g., Lehmann, Bassett, Sands, Spencer, & Gliner, 1999), systems-oriented examinations of US National data (e.g., Wells et al, 2003), and the development of parent surveys about transition (e.g., Glidden & Jobe, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the large-scale studies involving parents have provided few findings related to parent involvement in the transition process or post-school life for the young adult with disability and their families. In the United States, research has been focused on areas such as parent involvement in transition planning (e.g., Geenen, Powers, & Lopez-Vasquez, 2001), evidence-based practices for increasing student involvement in the transition process (e.g., Lehmann, Bassett, Sands, Spencer, & Gliner, 1999), systems-oriented examinations of US National data (e.g., Wells et al, 2003), and the development of parent surveys about transition (e.g., Glidden & Jobe, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Lehmann, Bassett, Sands, Spencer, and Gliner (1999) identified student, school, and family factors that individually and collectively predicted student participation in the transition planning process. The strongest predictors for student involvement in the transition planning process included (a) students’ goal-attainment skills, (b) students’ job competence, (c) democratic and noncontrolling family interactions, (d) family valuing enhanced student engagement, and (e) students attending and receiving special education services in general education classes.…”
Section: Student Engagement In Transition Planningmentioning
confidence: 99%
“…Lehmann et al (1999) found that providing opportunities at school for students to learn goal-attainment skills and to attain their goals predicted student engagement in transition planning meetings. Goff, Martin, and Thomas (2007) found that high school students who were Black and at high risk for dropping out of school were able to overcome the burden of acting White by setting and working toward attaining their postschool transition goals.…”
Section: Benefits Of Students Attaining Annual Transition Goalsmentioning
confidence: 99%
“…Students' experiences and insights have the potential to supply valuable resources for improving and refining services (Chambers et al, 2007;Morningstar, Turnbull, & Turnbull, 1995). With intentions similar to those promulgating facilitation of student-directed planning, researchers have listened to and shared the students' perceptions about the transition process (Benz, Lindstrom, & Yovanoff, 2000;Lehmann, Bassett, Sands, Spencer, & Gliner, 1999;Powers, Turner, Matuszewski, Wilson, & Loesch, 1999;Trainor, 2005).…”
mentioning
confidence: 99%